The right to adequate housing : making sense of eviction procedures in the context of rental housing after Ndlovu V Ngcobo - Louw, Jacobus Francois (Stellenbosch : University of Stellenbosch, 2011)
Thesis (LLM (Law))--University of Stellenbosch, 2004.